COMPARISON OF SOCIAL SCIENCE STUDY OUTCOMES USING A MAKE A MATCH MODEL WITH HANDOUT-ASSISTED SNOWBALL THROWING - Fitriani Yulianti; Fitri Oktaviansyah (Journal Learning Geography, 2023)
Various learning models can eliminate students' boredom while learning. The make a match and snowball throwing learning models are learning models that use a game system. The problem in this study is whether the social studies integrated learning outcomes using the make a match model are better than the snowball throwing learning model assisted by handout media for class VIII students of SMP Negeri 18 Banda Aceh. This study aims to find out whether the learning outcomes of integrated social studies using the make a match learning model are better than the snowball throwing learning model assisted by media handouts for class VIII students of SMP Negeri 18 Banda Aceh. This study uses a quantitative approach, with the type of experimental research. Sampling was taken using purposive sampling technique, two classes were taken from class VIII-4 and VIII-5, totaling 60 participants. Data collection techniques using pre-test data and post-test data. Data analysis techniques using the t test. The results of data processing obtained tcount ttable or 3.13 1.67 so that Ha is accepted. It can be concluded that the integrated social studies learning outcomes taught using the Make A Match learning model are better.